2017
DOI: 10.5217/ir.2017.15.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal surveillance interval after a colonoscopic polypectomy for the Korean population?

Abstract: Background/AimsWestern surveillance strategies cannot be directly adapted to the Korean population. The aim of this study was to estimate the risk of metachronous neoplasia and the optimal surveillance interval in the Korean population.MethodsClinical and pathological data from index colonoscopy performed between June 2006 and July 2008 and who had surveillance colonoscopies up to May 2015 were compared between low- and high-risk adenoma (LRA and HRA) groups. The 3- and 5-year cumulative risk of metachronous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…Facciorusso et al 96 97 reported a significantly increased risk with the presence of more than one AA at index (OR 3.22, 95% CI 2.19 to 5.39) and Jang et al 114 reported a statistically significant increase in the odds of AA at first surveillance with increasing number of adenomas at index. However, Atkin et al 31 32 reported no significant association for three or four adenomas versus one adenoma, and three further studies reported no significant associations for any comparisons 106 109 115…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Facciorusso et al 96 97 reported a significantly increased risk with the presence of more than one AA at index (OR 3.22, 95% CI 2.19 to 5.39) and Jang et al 114 reported a statistically significant increase in the odds of AA at first surveillance with increasing number of adenomas at index. However, Atkin et al 31 32 reported no significant association for three or four adenomas versus one adenoma, and three further studies reported no significant associations for any comparisons 106 109 115…”
Section: Resultsmentioning
confidence: 97%
“…The findings were inconsistent. Seven studies, ranging in size from 47 to 11 944 patients, presented evidence relating to the risk of AA at first surveillance 31 32 95 106 109 113–115. Only one of these106 reported a statistically significant increased risk for proximal adenomas at index versus either non-advanced adenoma or no adenoma (AA vs non-AA at first surveillance: RR 1.58, 95% CI 1.11 to 2.25; AA vs no adenoma at first surveillance: RR 1.84, 95% CI 1.31 to 2.59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening colonoscopy and polypectomy are known to produce the most significant effects on reducing the incidence and mortality of colorectal cancer (CRC) . Patients who have one or more adenomas removed are at an increased risk for developing metachronous advanced adenomas or cancer, and thus, these patients are recommended to undergo follow‐up surveillance colonoscopy . Current guidelines regarding post‐polypectomy surveillance have introduced the concept of risk stratification on the basis of baseline adenoma characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Patients who have one or more adenomas removed are at an increased risk for developing metachronous advanced adenomas or cancer, and thus, these patients are recommended to undergo follow-up surveillance colonoscopy. [3][4][5][6] Current guidelines regarding post-polypectomy surveillance have introduced the concept of risk stratification on the basis of baseline adenoma characteristics. 3,5,6 These guidelines stratify adenomas into two risk groups and recommend a surveillance colonoscopy every 10 years in individuals without adenomas, every 5-10 years in patients with low-risk adenomas, and every 3 years in those with high-risk adenomas.…”
Section: Introductionmentioning
confidence: 99%